Evaluating community ORT programmes: indicators for use and safety - Chowdhury, AMR (© 1986 Oxford University Press, 2019)
Community-based oral rehydration programmes to reduce diarrhoea-related mortality have been initiated in many developing countries in recent years. However, to date few evaluation studies have been carried out on these programmes and there is poor standardization in the indicators used. This paper discusses mainly the problems surrounding the intermediate process indicators: availability of ingredients; people's perceptions about diarrhoea and its treatment; and knowledge, safety and usage of oral rehydration solutions (ORS), with usage being discussed in some detail. Impact indicators based on mortality are discussed more briefly. Although most evaluations have studied the mortality impact of these programmes, it is suggested that programme evaluations should initially concentrate on process indicators to demonstrate how well the programme has been implemented. Only when implementation is successful and usage of ORS per diarrhoea episode is high can there be an appreciable impact on mortality.